Finite element analysis of residual stress from welding process - Tan, Kok Keat (2018)
This study investigates residual stress from welding processes which are butt welding and laser cladding with the use of finite element software, ANSYS parametric design language. Two models were simulated for each welding process. First model does not take into account material addition during the welding process and the second model does with the use of element birth/death. Longitudinal and transverse residual stresses were then plotted and compared with temperature gradient and a strong relationship has been observed for both welding processes, with longitudinal residual stress being the dominant stress.